Cervical mobility and suboccipital space C0-C1 in patients with headache - O'Brien-Masias, Felipe (2022)
Introduction: headaches are a public health problem and the role of cervical biomechanics in their condition has been postulated. Objective: it was to evaluate the association between the presence of headache with cervical mobility and the alteration of the suboccipital space C0-C1. Material and methods: the design was case-control; the population was adults between 18 and 59 years old who worked in the administrative field. The cases were made up of workers with headache, controls workers without this symptomatology. Cervical mobility measured with the Cervical Range of Motion Instrument CROM3 and the measurement of the C0-C1 space by lateral teleradiography were evaluated. Results: 55 controls and 28 cases participated. A greater presence of cervical pain was found in the cases (p < 0.001); the cases presented a 64.3% of important or very severe impact of disability, an OR of 4.76 was found for the category of presenting space decreased in C0-C1 adjusted to sex, age and presence of cervical pain. Conclusions: the decrease in left lateralization, the increase in suboccipital flexion, as well as the decrease in the C0-C1 space, were associated with a greater probability of presenting headache.